Glycine Receptors Containing α2 or α3 Subunits Regulate Specific Ethanol-Mediated Behaviors - Blednov, Yuri A. (J Pharmacol Exp Ther, 2015)
Glycine receptors (GlyRs) are broadly expressed in the central nervous system. Ethanol enhances the function of brain GlyRs, and the GlyRα1 subunit is associated with some of the behavioral actions of ethanol, such as loss of righting reflex. The in vivo role of GlyRα2 and α3 subunits in alcohol responses has not been characterized despite high expression levels in the nucleus accumbens and amygdala, areas that are important for the rewarding properties of drugs of abuse. We used an extensive panel of behavioral tests to examine ethanol actions in mice lacking Glra2 (the gene encoding the glycine receptor alpha 2 subunit) or Glra3 (the gene encoding the glycine receptor alpha 3 subunit). Deletion of Glra2 or Glra3 alters specific ethanol-induced behaviors. Glra2 knockout mice demonstrate reduced ethanol intake and preference in the 24-hour two-bottle choice test and increased initial aversive responses to ethanol and lithium chloride. In contrast, Glra3 knockout mice show increased ethanol intake and preference in the 24-hour intermittent access test and increased development of conditioned taste aversion to ethanol. Mutants and wild-type mice consumed similar amounts of ethanol in the limited access drinking in the dark test. Other ethanol effects, such as anxiolysis, motor incoordination, loss of righting reflex, and acoustic startle response, were not altered in the mutants. The behavioral changes in mice lacking GlyRα2 or α3 subunits were distinct from effects previously observed in mice with knock-in mutations in the α1 subunit. We provide evidence that GlyRα2 and α3 subunits may regulate ethanol consumption and the aversive response to ethanol.